Conservative management for adherent placenta after live birth in angular or interstitial pregnancies: A new entity "angular placenta attachment" - Erika Nakatsuka; Kazuya Mimura; Masayuki Endo; Tatsuya Miyake; Aiko Kakigano; Shinya Matsuzaki; Yoko Kawanishi; Takuji Tomimatsu; Tadashi Kimura (Elsevier, 2020)
Objective: Angular and interstitial pregnancies have been reported with live births and are often complicated by adherent placentas. Most cases had been treated with hysterectomy or corneal resection. Case report: We successfully treated four patients with conservative management (including one reported previously). Case 1 had a vaginal delivery, but the placenta remained attached. We maintained the patient under observation and delivered the placenta on postpartum day 9. Case 2 underwent a C-section. Uterine artery embolization controlled the hemorrhage without placenta removal. The placenta had disappeared by postpartum day 136. Case 3 underwent a C-section. The right uterine angle, where the placenta was attached, was bulging. We manually removed the placenta. Conclusion: We propose a new entity in angular or interstitial pregnancies called "angular placenta attachment" that could be diagnosed during C-sections or after vaginal delivery without placental separation. Expectant management may be considered for adherent placentas in these cases.